ChemInform Abstract: Direct Conversion of Methylarenes into Dithiocarbamates, Thioamides and Benzyl Esters. Issue 40 (30th September 2014) - Guntreddi, Tirumaleswararao; Vanjari, Rajeshwer; Singh, Krishna Nand
Abstract Initial treatment of methylarenes with NBS and catalytic amounts of tBuOOH followed by reaction with carboxylic acids, S8 and amine, or CS2 and amine allow the synthesis of benzyl esters, thioamides and dithiocarbamates.